Foreign direct investment, domestic savings, and economic growth: The case of Turkey - Taspinar, Nigar (International Economic Society ies@econ-society.org, 2014)
The present study investigates long run equilibrium relationship between real income growth, foreign direct investment, and domestic savings in Turkey, which has a developing economy. Bounds tests confirm that foreign direct investments and domestic savings are in long term equilibrium relationship with real income growth. Domestic savings have positive, statistically significant, and inelastic impact on real income both in the long term and short term of the Turkish economy whereas foreign direct investments do not. Error correction model reveals that real income of Turkey converges to its long term equilibrium level by 93.2% (which is very high) by the contribution of foreign direct investment and domestic savings. Finally, conditional Granger causality tests reveal that changes in foreign direct investments and domestic savings in Turkey preceede changes in real income. Furthermore, domestic savings in Turkey are foreign direct investments driven in the short term of the Turkish economy. © 2014, International Economic Society.
Keywords: Domestic Savings; Foreign Direct Investment; Real Income; Turkey